A Different Path to the Same Old Question: Why Should Cartels be Criminalised? - Marques, Nuno Castro (2017)
Regardless of the extreme negative qualifications usually attributed to cartels and bid rigging, EU and Portuguese competition laws do not set them apart from other anticompetitive practices regarding the possible applicable sanctions. EU and Portuguese competition laws establish the same potential sanctions for all competition infringements. Despite that, there are clear indications that EU and Portuguese legislators intend to treat cartels differently from all other competition infringements. Despite that, there are clear indications that EU and Portuguese legislators intend to treat cartels differently from all other competition infringements, but those differences have essentially to do with rules or procedures designed to facilitate their detection, production of evidence and decision-making. Notwithstanding the relevance of the “traditional” arguments regarding cartel criminalization, we consider that the discussion is still incomplete and would benefit from the inclusion of an additional “filter”. As it is a discussion about a criminalization process, the use of common instruments in criminology can shed more light into the question, and one of those instruments – or the most important one – is the analysis of the legal interests protected by the norm. We deem it essential to think about what legal interests are harmed in each of the different types of competition infringements, so as to conclude if indeed and to what extent cartels and bid rigging are capable of impairing more or different legal interests, or in a different intensity, than those potentially violated by other types of competition infringements. The conclusion is that cartel and bid rigging conducts always infringe the entire set of legal interests that is or may be defended by competition laws and always do so with high intensity.